CRIMINAL RESPONSIBILITY OF BUSINESS ACTORS FOR ILLEGAL MINING CRIMINAL ACTS - Makmudin, Makmudin; Purnawan, Amin (Jurnal Hukum Khaira Ummah, 2024)
The purpose of this study is to determine and analyze the criminal liability of business actors for illegal mining crimes. To determine and analyze the weaknesses of criminal liability of business actors for illegal mining crimes. To overcome and analyze the criminal liability of business actors for illegal mining crimes in the future. The method used by the researcher is a normative legal approach and the specifications in this study are descriptive-analytical. The data sources in this study are secondary data obtained from literature studies. Data are analyzed qualitatively. Based on the results of the study that Based on the descriptions that the author has put forward in the discussion chapter, the author concludes that the criminal liability of business actors for illegal mining crimes is with civil sanctions and also administrative sanctions by revoking business licenses. The weakness of criminal liability of business actors for illegal mining crimes is the difficulty of proving the element of error. This is because the subject of corporate law is different from humans who have reason and thoughts. Criminal liability of business actors for illegal mining crimes in the future is regulated in Article 158 of Law Number 3 of 2020, mining business actors without IUP can be sentenced to a maximum of 10 years in prison and a maximum fine of IDR 10 billion. The application of strict and appropriate criminal sanctions can be an effort to prevent illegal mining in the future.